Spectrum Sensing Under Different Fading Channels Using Energy Detection Technique - Harikrishnan, R; Padmathilgam, V (International Journal of Computer Sciences and Engineering, 2025)
In this wireless era there is an exponential increase in wireless devices but the spectrum availability for these devices has become very less. Some additional spectrum band for these devices is required to make communication possible. To clear this spectrum demand the cognitive user access the unused licensed frequency band, when the band is free. The cognitive users may utilize unused channel till the band is occupied by primary user. In this paper, A MATLAB based simulation is carried out to appraise the detection performances of cognitive radio .The spectrum sensing in non fading Additive White Gaussian Noise (AWGN) environment and different fading scenarios such as Rayleigh, , Rican, Log normal shadowing Weibull and Hyot fading environment using energy detection technique are carried out. The performance analysis of energy detector designed for Average Signal-to-Noise Ratio (SNR) and different fading parameters are analyzed in provisions of Probability of missed detection (Pm) and Probability of false alarm (Pf).The spectrum sensing is analyzed by comparing the performances of various wireless fading channels.